A Changhsingian (late Permian) nautiloid assemblage from Gujiao, South China. (25th September 2019) - Miao, Luyi; Dai, Xu; Korn, Dieter; Brayard, Arnaud; Chen, Jing; Liu, Xiaokang; Song, Haijun
Abstract: A c . 0.30 m thick cherty limestone bed in the Dalong Formation at Gujiao (Guizhou) has yielded a highly diverse Changhsingian nautiloid assemblage. Its age is late Changhsingian, indicated by the co‐occurring ammonoid Pseudotirolites sp. This assemblage is composed of nine species and five taxa in open nomenclature in nine genera, including one new genus and three new species: Neotainoceras zhaoi sp. nov., Nodopleuroceras gujiaoense sp. nov. and Gujiaonautilus longliensis gen. et sp. nov. Sholakoceras is for the first time recorded in South China. Compared with literature data from 52 sites in various regions worldwide, the material described here presents the most diverse Changhsingian nautiloid assemblage. Among the genera of the Gujiao assemblage, Pleuronautilus,   Tainoceras and Liroceras are cosmopolitan, while the others are more endemic or genera known so far only from South China.